Calcium Intakes in the Diet of Eastern Morocco’s Population - El-Houcine Sebbar; Hicham Sam; Zaina Sidqi; EnnouamaneSaalaoui; Mohammed Choukri (Journal of Pharmacy and Nutrition Sciences, 2018)
Purpose: Osteoporosis is the most common bone disease in the world. Most epidemiological studies show that calcium and vitamin deficiencies are very frequent not only in the elderly population but also in the general adult population. The aim of our work was to evaluate the calcium intake in population of eastern Morocco by the translated version in Moroccan Arabic dialect of Fardellone questionnaire. Methods: The version translated into Arabic dialect Fardellone questionnaire was tested on a sample of 1000 subjects. The age distribution was calculated on the distribution of the general Moroccan population according to the most recent population and housing census of September 2014. Therefore, subjects younger than 15 years represented the first age group, the subjects aged 16 to 59 years represented the second age group and the subjects older than 60 years represented by the third age group. Results: The study population included 56% women (n = 560), 44% of men (n = 440). The subjects aged less than 15 years accounted for 11% (n = 110), those aged 15 to 59 73.1% (n = 731) and those aged over 60 years 15.9% (n = 159). The mean calcium intake was respectively 4907 mg by week (that means 701 mg/day). The assessment of calcium intake by age group showed a deficiency in all three groups. The average consumption of calcium per day was significantly lower than the recommended daily amount for the three age groups. Patients aged over 60 years is the age group most under nourished calcium. The comparison of both gender found a deficit higher among women than among men. Conclusion: Evaluation of the calcium intake is an essential tool for better management of metabolic bone diseases.